63+8(6x-1)=7(6x+1)

Simple and best practice solution for 63+8(6x-1)=7(6x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 63+8(6x-1)=7(6x+1) equation:


Simplifying
63 + 8(6x + -1) = 7(6x + 1)

Reorder the terms:
63 + 8(-1 + 6x) = 7(6x + 1)
63 + (-1 * 8 + 6x * 8) = 7(6x + 1)
63 + (-8 + 48x) = 7(6x + 1)

Combine like terms: 63 + -8 = 55
55 + 48x = 7(6x + 1)

Reorder the terms:
55 + 48x = 7(1 + 6x)
55 + 48x = (1 * 7 + 6x * 7)
55 + 48x = (7 + 42x)

Solving
55 + 48x = 7 + 42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42x' to each side of the equation.
55 + 48x + -42x = 7 + 42x + -42x

Combine like terms: 48x + -42x = 6x
55 + 6x = 7 + 42x + -42x

Combine like terms: 42x + -42x = 0
55 + 6x = 7 + 0
55 + 6x = 7

Add '-55' to each side of the equation.
55 + -55 + 6x = 7 + -55

Combine like terms: 55 + -55 = 0
0 + 6x = 7 + -55
6x = 7 + -55

Combine like terms: 7 + -55 = -48
6x = -48

Divide each side by '6'.
x = -8

Simplifying
x = -8

See similar equations:

| -8(b-862)=-560 | | 16=8c | | 2.50(m+15.00)=662.5 | | 2.5r=95 | | 6(3x-6)=10x | | a+3ab+6+7a-2ab-1=0 | | 75+5x=10x+100 | | 9b-7b+6=-4b+78-3b | | 11x-160=56-7x | | 10+58=6x+2 | | 2x^4+3x-50=0 | | 5a+4b-5(7a-9b)= | | 26w+20=956 | | X-2x=125 | | (1+y)x^2-3yx+(1-y)=0 | | 2.50(m+15.00)=412.5 | | 84=2x-4+2x+4 | | 75=4529 | | -1-10r^2=-881 | | 3.4=y+2.1 | | -3x^2+8x-6=0 | | -8p-8=-14-7p | | -2x+(-21)=23 | | -1-10r^2=881 | | 84=4x^2-8+8-16 | | 929=97+13r | | 31/2(6x-21/2)+51/3=-62/3(-3x+16/5)+122/3 | | -70=-2(n+5)+7(4-6n) | | 21m-9= | | 15(b+17)=555 | | 7(f+37)=693 | | -147=-5x-4(-5x+18) |

Equations solver categories